THE EFFECT OF MANAGERIAL OWNERSHIP, EARNINGS PERSISTENCE AND INVESTMENT OPPORTUNITY SET ON EARNINGS QUALITY - Iis Nurjanah; Nugroho Heri Pramono (Jurnal Akuntansi dan Ekonomi Bisnis, 2026)
This study focuses on companies in the property and real estate sectors listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. It aims to examine the effect of managerial ownership, earnings persistence, and investment opportunity set on earnings quality. Using secondary data and purposive sampling, this quantitative study selected eight companies as samples. Data were analyzed using multiple linear regression with EViews 12. The results show that managerial ownership, earnings persistence, and investment opportunity set simultaneously have a significant effect on earnings quality. Partially, managerial ownership has no significant effect on earnings quality, while earnings persistence has a significant positive effect, and investment opportunity set has a significant negative effect on earnings quality.